Tell el-Hesi: A type site for reevaluating so-called 'Egyptian Governors' Residencies' of the south - Blakely, Jeffrey A. (Palestine exploration quarterly, 2018)
In 1984 Eliezer Oren identified a series of structures found at 13th and 12th centuries BCE sites of southern Canaan, calling them Egyptian Governors' Residencies. He identified Bliss's City IV as a defining site. In 2000 Blakely identified Petrie's Pilaster Building as a second example from Tell el-Hesi. It is now clear that Bliss's City IV dates to the 13th century and that some of its architectural elements were salvaged after its destruction to build Petrie's Pilaster Building in the 12th century. All of the southern examples are found in an agricultural zone of uncertainty where there is no clear likelihood of a harvestable crop in any given normal year. As it happens, the 13th and especially the 12th centuries BCE were far from normal, being a period of drought and extreme drought. Thus no crops could have been expected. This suggests the structures could not have been centres for the collection of a grain harvest tax, the accepted view. Rather, one wonders if the sites did not monitor a large pasturage.